MODERN WOUND DRESSING FOR WOUND INFECTION: AN OVERVIEW - Rizani, Novida (Indonesian Journal of Tropical and Infectious Disease, 2012)
When the tissue of skin is break means a wound is happens. To seal it, many choices of wound healing are available. Moist wound dressing can be better optional than the conservative ones. A bioactive agent that being added at the dressing in fact can increase healing rate of wound, moreover can subjugate wound infection caused by the pathogens, and also capable to prevent it. In this review, there are summary of modern moist wound healing, the wound pathogens, and some of sturdy bioactive agent for wound dressing. The treatment of wound infections using impregnated wound dressing by bioactive agent can also by antimicrobial agent that will striven against bacteria colonial.